Seed germination and emergence ecology of Monochoria vaginalis (Burm. f.) Kunth - Athira, G.R.; Menon, Meera V.; Sindhu, P. V.; Prameela, P. (Journal of Tropical Agriculture, 2020)
Monochoria vaginalis is a noxious herbaceous semi aquatic weed in the family Pontederiaceae, present in paddy fields throughout the rice growing areas of the world. A study was conducted to determine the effect of depth of burial, pH, salinity, flooding, light and temperature on germination of Monochoria vaginalis. Monochoria seeds germinated on soil surface, but not when placed below 2 cm depth. The germination was found to be higher in solutions of pH 6 and 7, but seeds did not germinate when immersed in buffered solutions of pH 4, 5, 8, and 9. Saline solutions with concentrations ranging from 25 to 250 mM NaCl inhibited the germination. Seeds kept in continuous dark condition failed to germinate irrespective of the temperature provided. Monochoria seeds germinated at a temperature of 38oC in continuous light, and in alternate light and dark condition. Seed germination in Monochoria was significantly influenced by flooding depth and duration. Greater germination was obtained when seeds were kept in saturated soil condition and low flooding depth (i.e., less than 5 cm) for more than 4 days.